Light-harvesting, 3rd generation RuII/CoII MOF with a large, tubular channel aperture - Bradley, Louise; Schmitt, Wolfgang (My University, 2019)
A photoactive, hetero-metallic CoII/RuII-based metal–organic framework (MOF) with a large channel aperture, ca. 21 Å, is reported. The photophysical properties of the MOF are derived from the RuII nodes giving rise to emission centred at ca. 620 nm and relatively long triplet 3MLCT lifetimes. In addition to the optical attributes, the 1H-imidazo [4,5-f][1,10]-phenanthroline ligand imparts structural functionality to the MOF which is composed of alternating CoII- and RuII-based nodes of Δ and Λ helicity. The framework maintains its integrity upon activation and shows gas sorption behaviour that is characteristic of mesoporous materials promoting high CO2 sorption capacities and selectivities over N2.
PUBLISHED